MODERN PROBLEMS AND INNOVATIVE SOLUTIONS OF THE OIL REFINING INDUSTRY: A NEW APPROACH IN THE ERA OF GLOBAL CHANGES - Badritdinova Farida Makhamatdinovna; Makhmudova Mohira Davronbek qizi; Mo'minkulova Madina G'ayratjon qizi (Web of Journals Publishing, 2025)
This in the article oil again work industry in today's global environment current problems , technological transformation processes , carbon neutrality requirements , raw materials of quality decrease , product diversification and energy efficiency issues analysis Statistical information , advanced factories experience , new catalytic processes and innovative integration models based on modern solutions offer Article previously there is scientific from work different accordingly oil again work process new global energy paradigm in the context of analysis does.
Keywords: Oil refining industry, modern challenges, innovative solutions, global changes, energy transition, sustainable refining, digitalization in oil refining, circular economy, low-carbon technologies, petrochemical integration, environmental impact reduction, advanced catalysts, process optimization.